Dooghe, G. y Helander, J. (editores). Family Life in Old Age. Netherlands Interuniversity Demographic Institute : y Population and Family Study Center, 1979. - Ham Chande, Roberto (Estudios Demográficos y Urbanos, 1982)
DOOGHE, G y HELANDER, J. (editores), Family life in old age. Netherlands Interuniversity Demographic Institute y Population and Family Study Center, 1979.